Robot-assisted Heller's myotomy for achalasia in children. Issue 1 (1st January 2016) - Altokhais, Tariq; Mandora, Hala; Al-Qahtani, Ayed; Al-Bassam, Abdulrahman
Abstract: Background: Achalasia is rare in children. Surgical options include open, laparoscopic and robotic approaches. However, Heller's myotomy remains the treatment of choice. This report describes our experience with robot-assisted Heller's myotomy in children and presents a review of the literature. Methods: Included in this study are children who underwent robot-assisted Heller's myotomy for esophageal achalasia via the Da Vinci surgical system between 2004 and 2015 at King Saud University Medical City, Riyadh, Saudi Arabia. The medical records of these patients were reviewed for demographic data, presenting symptoms, diagnostic modalities, operative procedures, complications, outcomes and follow-ups. Results: Six patients were identified. The age of the patients at surgery ranged between 2 and 12 years (mean 7.1 years). The most common presenting symptoms were dysphagia, vomiting and nocturnal cough. Contrast swallow and upper gastrointestinal endoscopy established a diagnosis of esophageal achalasia in all of the patients. Four patients underwent esophageal dilatation 2–5 times before the definitive procedure. All patients underwent successful robot-assisted Heller's myotomy with concomitant partial posterior fundoplication. The postoperative course was uneventful. Five patients had a complete resolution of the symptoms and one patient improved. The follow-up assessments have been consistent and have ranged from 0.5 to 11 years (mean 4.4 years). Conclusion: Robotic-assisted Heller's myotomy for esophageal achalasia in children is safe and effective and is a suitable alternative to open and laparoscopic approaches.